Identifying major phases in the use of land, energy and changing landscapes by agrarian societies (7,000 cal BP-Present) in Cantabrian Spain, based on cultural changes and anthropogenic signals - Martinez, Alexandre; Zapolska, Anhelina; Arthur, Frank; Verhagen, Philip; Kluiving, Sjoerd; Muñoz-Rojas, José; Borja Barrera, César; Fraile Jurado, Pablo (Frontiers in Environmental Archaeology, 2024)
Introduction Enacting transitions toward more sustainable management and use of land, energy, and natural resources poses multiple challenges for human societies. Such transitions have been a constant throughout human history and therefore there is a need to learn from them and apply that knowledge to current land-use policies and management. Significant human impact on landscape and environment in Cantabrian Spain has been documented in alignment with the Neolithization (ca. 7,000 cal BP). While the classic approach of identifying cultural phases based on historical and archaeological data has been extensively studied, much less is understood on how such phases are dependent upon increasing anthropogenic influence on the environment. Methods Cantabrian Spain is well-known for its long mining history. Key processes historically shaping landscapes in the region include the implementation of mining/metallurgy industries and extraction of forest resources. These historical processes were characterized, respectively using heavy metal pollution contents (Hg, Zn, Cd, As, Ni, REE, Pb, and 206 Pb/207 Pb) and total arboreal pollen percentages in peat bogs, providing global trends of human impact on the environment. These trends were then compared to climate (temperature and precipitation) and natural vegetation evolution modeling through time. Results Results show seven phases of major human impact on the environment: (1) the Copper phase ca. 4,400–4,100 cal BP, (2) the Middle Bronze phase ca. 3,500–3,150 cal BP, (3) the Iron phase ca. 2,800–2,500 cal BP, (4) the Roman phase ca. 2,200–1,750 cal BP, (5) the Medieval phase ca. 1,250–1,000 cal BP, (6) the Colonial phase ca. 650–400 cal BP, and (7) the Industrial phase ca. 150 cal BP-Present. Discussion Four phases are tightly related to substantial changes in land use and subsistence strategies: (1) Production, with the appearance of productive economies during the Neolithic, (2) Specialization, with the appearance of specialized activities and trade during the Middle Bronze phase, (3) Urbanization, with the first urban centers during the Roman phase, and (4) Globalization, with worldwide colonialism and capitalism economies during the Colonial phase.